Financial Behavior in the Digital Economy Era: Financial Literacy and Digital Literacy - Deri Firmansyah; Dwinanto Priyo Susetyo (PT FORMOSA CENDEKIA GLOBAL, 2022)
Disruptive technology in Industry 4.0 (I4.0) continues to occur, now the world is entering a new chapter in the digital economy era, and it is even underway. Every individual, community, company or region with a different identity, is in his arms. Limited access to resources in the world's economy reveals the importance of financial literacy (FL) and its behavior in managing finances, as well as the adequacy of digital literacy (DL) to achieve success and get out of the trap of paradigm and necessity in this era. This study presents relevant literature on the concept and determinants and determinants of FL and DL. It also presents literature showing the relevance of FL and DL to financial behavior (FB) and financial decisions in the digital economy era. To fulfill this aim, systematic literature reviews were conducted. The findings, that from various perspectives, intersections and different views regarding the concepts of FL and DL, the determinants and determinants of the three, but the core concepts are basically the same according to context, interpretation and practice.